Judicial review of regulatory decisions: Decoding the contents of appeals against agencies in Spain and the United Kingdom - Luis E. Mejía (Regulation & Governance, 2021)
Despite the important role that courts play to supervise the legality of regulatory agencies' actions, only few comparative studies analyze the contents of judicial appeals against regulatory decisions within European countries. This paper builds on the comparative administrative law scholarship and administrative capacities literature to analyze the content of 2,040 rulings against decisions issued by competition and telecommunications regulators in Spain and the United Kingdom. To understand the substance of the appeals, the study classifies cases according to the alleged administrative principles under breach and the regulatory capacities under challenge. Findings show a clear country-sector variation regarding the information contained in judicial disputes for both dimensions of analysis, which can be explained as a result of existing differences between the institutional settings of courts. These results offer a more in depth understanding of the political role of judicial oversight over regulatory agencies embedded in different institutional arrangements and policy sectors.
Keywords: 330; administrative law; competition; judicial review; regulatory agencies; telecommunications